(untitled) (Journal of the College of Basic Education, 2022)
The aim of the research is to identify the level of alert thinking associated with health protection among students of the Department of Educational and Psychological Sciences at the University of Karbala. And also the statistically significant differences in the level of alert thinking related to health prevention among students of the Department of Educational and Psychological Sciences at the University of Karbala according to the gender variables (students - students) and the classroom. The research was applied to (200) male and female students, and to achieve the research objectives. The Mindfulness Thinking Scale Related to Health Prevention was prepared by the researcher. The results showed that the members of the research sample for the sample as a whole. Students in the Department of Educational and Psychological Sciences are not characterized by mindful thinking related to health protection. The students have the least expression of attentive thinking related to health protection than the female students. I recommend researching interest in educational and counseling programs to raise mindful thinking related to health aspects. And attention to educating students more than girls through awareness programs and educational focus on mindful thinking. It is also necessary to conduct a semi-experimental study on the variable of developing attentive thinking and electronic academic identity for university students as a whole. The alert thinking variable was used on a higher class of students, it was teachers or senior administrative officials at the university